(untitled) (Research, Society and Development, 2021)
Objective: Analyze the association between bullying and weight changes in adolescents. Methodology: Cross-sectional study, involving adolescents from the state education system of Olinda, aged between 14 and 19 years and both genders. The instrument used was PeNSe and anthropometric assessment. Results: For analysis of bullying, male adolescents (23.1%), between 14-16 years of age (26.3%) and obese (44%) were more affected. Among the variables analyzed, only BMI was statistically significant for suffering school bullying. When it comes to cyberbullying, most were female (9.8%), aged between 17-19 years (11.8%) and obese (16%). Unlike bullying, the analyzed variables were not statistically significant for the practice of cyberbullying. Discussion: Regarding gender, it was observed in the present study a homogeneous distribution between females and males, in cases of both bullying and cyberbullying. Regarding age, being younger (14-16 years) is considered a mitigating factor as those with overweight/obesity to become victims of bullying, unlike cyberbullying, which had mostly young people between 17-19 years old. Conclusion: The practice of bullying damages the mental and physical health of these young people who are in a developmental stage.